FEEDING ACTIVITY AND GROWTH EFFICIENCY OF COMMON CARP (CYPRINUS CARPIO LIN.) EXPOSED TO SYNTHETICS DETERGENT (LAS) - Sunardi .. .; Darmadi Goenarso (BIOTIKA Jurnal Ilmiah Biologi, 2002)
A study on feeding activity and growth efficiency of common carp (Cyprinus carpio) exposed to synthetics detergent Linear Alkyl Sulphonate (LAS) has been conducted. The period of the experiment was 30 days with 6-day observation interval. Fishes were tested in three different concentrations of LAS i.e. 0.5, 1.5, and 4.5 ppm. Feeding rate (FR), absorption efficiency (AE), production rate (PR) and growth efficiency (GE) were measured. The results showed that the increased of LAS concentration decreased FR from 51.74 (control) to 40.27 mg.g bw-1.d-1 (22.17 %) in treated fish. LAS also reduced AE from 94.88% to 87.84% (6.89%). In addition, LAS decreased PR from 2.70 to 1.03 mg.g bw-1.d-1 (61.85%0 and GE from 5.21 to 2.58% (50.48%).